1985
DOI: 10.2224/sbp.1985.13.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Norm Formation, Social Conformity, and the Confederating Function of Humor

Abstract: The following analysis was carried out in two parts. First, a quantitative measure was developed of the strength of the tendency toward conformity within social groups exposed to ambiguous situations. And second, two experiments were conducted in an attempt to reproduce empirically the confederating function of humor hypothesized in groups facing such situations. Exactly what is the effect of the opinions of others in the joking situation on our own? The results of these experiments are clear-cut. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In other words, a desire to maintain a positive social identity may have led women to denigrate men by suggesting lack of intelligence is more typical of "them" than of "us." In this way, the jokes and the presumed laughter may have served as a unifier for women (Khoury, 1985;Stillman, Baumeister, & DeWall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a desire to maintain a positive social identity may have led women to denigrate men by suggesting lack of intelligence is more typical of "them" than of "us." In this way, the jokes and the presumed laughter may have served as a unifier for women (Khoury, 1985;Stillman, Baumeister, & DeWall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When the receiver switches to a noncritical mindset, he or she tacitly consents to a shared understanding (a social norm) that it is acceptable in this context to make light of sexismÐto treat it in a light-hearted, noncritical manner (see Emerson, 1969;Francis, 1988;Khoury, 1985 for similar arguments regarding the communication of socially inappropriate sentiments through humor). The receiver's acceptance of the sexist humor, then, contributes to the construction of an implicit local norm of tolerance of sexism.…”
Section: Effects Of Sexist Humor Upon Perceptions Of Social Normsmentioning
confidence: 99%
“…Thus, sexist humor communicates an implicit normative standard that, in this context, one can treat sex discrimination in a less serious, more lighthearted manner. Recipients who approve of the humor—switch to a non-serious humor mind-set to interpret it—assent to the norm implied by the humor that it is permissible in this context to make light of discrimination against women (Emerson, 1969; Khoury, 1985; Meyer, 2000). Indeed, Ford (2000) found that sexist humor increased tolerance of a sexist event, but not when participants were instructed to interpret the humor as they would a serious, non-humorous message.…”
Section: Introductionmentioning
confidence: 99%